The agent's deadly liaison - Bokal, Jennifer D. (Bokal, Jennifer D. Wyoming nights, 2022)
"A serial killer awaiting trial in prison wants to confess...but only to District Attorney Chloe Ryder and the Rocky Mountain Justice operative who arrested her. When Chloe and Marcus Jones arrive, their nemesis lays a deadly trap. Now Chloe's only hope of survival is the man who doesn't know she's pregnant from their one night together. But the killer does--and vows baby will never make three..."--Back cover.